Simulating an Applied Voltage in Molecular Dynamics Using Charge Optimized Many Body (COMB3) Potentials. (9th September 2015) - Antony, Andrew Charles; Akhade, Sneha A.; Liang, Tao; Janik, Michael J.; Maranas, Janna K; Sinnott, Susan B.
Abstract : The work presented here gives an atomic level description of applying an external voltage during a molecular dynamics (MD) simulation. We present the methodology behind simulating an applied voltage and implement the method to a Cu/H2 O (electrode/electrolyte) system. Water molecules are found to be less mobile at the interface due to a disruptive influence of metal-water interactions on the hydrogen bonded network found in bulk water systems but the effect of an applied voltage on the interfacial dynamics is found to be negligible. Molecular structure is determined by analyzing the degree of orientational ordering near the metal surface and it is concluded that the metal surface polarizes the molecules, causing an alignment of the molecular dipoles. Future results and additional analysis are also addressed towards the end of the results section.